2007
DOI: 10.1186/1744-859x-6-32
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes and opinions on the use of psychotropic medication in mental disorders of childhood

Abstract: BackgroundThe limited number of systematic, controlled studies that assess the safety and efficacy of psychotropic medications for children reinforce the hesitation and reluctance of parents to administer such medications. The aim of this study was to investigate the attitudes of parents of children with psychiatric disorders, towards psychotropic medication.MethodsA 20-item questionnaire was distributed to 140 parents during their first contact with an outpatient child psychiatric service. The questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…However, although professional practice guidelines exist, viewpoints of what constitutes appropriate treatment for ADHD are mixed, with some advocating stimulant medication as the most efficacious treatment and others favoring alternative approaches, including those who believe that stimulant therapy is overprescribed, unsafe, or unethical (Koelch, Schnoor, & Fegert, 2008;Taylor, O'Donoghue, & Houghton, 2006). Furthermore, despite evidence of efficacy, literature suggests that a substantial percentage of children who have been diagnosed with ADHD either do not begin medication prescribed for their core symptoms or fail to continue treatment (Jensen et al, 2007;MTA Cooperative Group, 2004 Studies examining barriers to initiation/maintenance of medication treatment of ADHD by parents have identified a plethora of factors, most notably lack of information, conflicting opinions (e.g., family members, teachers and health care providers), cost of medication, unsatisfactory experiences with health care providers, side effects, fear that prescription medicine leads to drug abuse, cultural beliefs, social stigma, and negative media portrayals of medication (Bussing, Gary, & Mills, & Garvin, 2003;Charach, Volpe, Boydell, & Gearing, 2008;DosReis & Myers, 2008;Johnston, Hommersen, & Siepp, 2008;Lazaratou, Anagnostopoulos, Alevizos, Haviara, & Ploumpidis, 2007;Leslie, Plemmons, Monn, & Palinkas, 2007;McNeal, Roberts, & Barone, 2000;Monastra, 2005;Pastor & Ruben, 2005;Stroh, Frankenberger, Cornell-Swanson, Wood, & Pahl, 2008). In essence, the literature to date suggests that parents' views of psychopharmacological treatment for ADHD are mixed, that misconceptions are common, and that making decisions regarding the use of medication is difficult.…”
Section: Introductionmentioning
confidence: 98%
“…However, although professional practice guidelines exist, viewpoints of what constitutes appropriate treatment for ADHD are mixed, with some advocating stimulant medication as the most efficacious treatment and others favoring alternative approaches, including those who believe that stimulant therapy is overprescribed, unsafe, or unethical (Koelch, Schnoor, & Fegert, 2008;Taylor, O'Donoghue, & Houghton, 2006). Furthermore, despite evidence of efficacy, literature suggests that a substantial percentage of children who have been diagnosed with ADHD either do not begin medication prescribed for their core symptoms or fail to continue treatment (Jensen et al, 2007;MTA Cooperative Group, 2004 Studies examining barriers to initiation/maintenance of medication treatment of ADHD by parents have identified a plethora of factors, most notably lack of information, conflicting opinions (e.g., family members, teachers and health care providers), cost of medication, unsatisfactory experiences with health care providers, side effects, fear that prescription medicine leads to drug abuse, cultural beliefs, social stigma, and negative media portrayals of medication (Bussing, Gary, & Mills, & Garvin, 2003;Charach, Volpe, Boydell, & Gearing, 2008;DosReis & Myers, 2008;Johnston, Hommersen, & Siepp, 2008;Lazaratou, Anagnostopoulos, Alevizos, Haviara, & Ploumpidis, 2007;Leslie, Plemmons, Monn, & Palinkas, 2007;McNeal, Roberts, & Barone, 2000;Monastra, 2005;Pastor & Ruben, 2005;Stroh, Frankenberger, Cornell-Swanson, Wood, & Pahl, 2008). In essence, the literature to date suggests that parents' views of psychopharmacological treatment for ADHD are mixed, that misconceptions are common, and that making decisions regarding the use of medication is difficult.…”
Section: Introductionmentioning
confidence: 98%
“…Informed participation in CMH services, for example, requires that parents understand factors influencing the development of their child's difficulties, the longer term course of these problems, the risks and benefits of different treatment options, and the skills they need to assist their child (Wills and Holmes-Rovner 2006). While parents (Lazaratou et al 2007;Sonuga-Barke and Balding 1993), like the general public (Pescosolido et al 2008), often lack accurate knowledge regarding CMH problems, those who are better informed find evidence-based treatments more acceptable (Bennett et al 1996) and are more likely to use available services (Andrews et al 1995;Corkum et al 1999;Johnston et al 2005). Materials teaching parenting skills, moreover, allow some parents to contribute to a significant reduction in their child's difficulties (Montgomery et al 2006).…”
mentioning
confidence: 99%
“…During the Hospitalization for Psychosis Phase, in working with parents, mental health providers may need to clarify existing confusion and emergent alternative explanations that may become detrimental to engagement and adherence to treatment plans. It is not surprising that parents begin to pursue information during this phase, especially as it relates to medication, as research has identified parental concerns about psychotropic medication (Lazaratou et al, 2007). Interventions at the parent level may need to include education around treatment specifics, information about prognosis, treatment, relapse, and the Downloaded by [Umeå University Library] at 14:55 03 April 2015 use of medication in the immediate and long term as they relate to their specific child and perceptions.…”
Section: Treatmentmentioning
confidence: 95%
“…In adolescents, this took the form of fear and hopelessness, and in parents, it appeared more frequently as grief and loss. Early intervention and inpatient treatment need to explore the fear and potential trauma experienced by patients and family members, including the fear of hospitalization and/or medication (Lazaratou et al, 2007;Townsend, Gearing, & Polyanskaya, 2012). This fear may be exacerbated by posttraumatic reactions to the experience of psychosis or the associated hospitalization, with rates of PTSD in response to early psychosis as high as 39%-66% (Mueser, Lu, Rosenberg, & Wolfe, 2010).…”
Section: Negative and Positive Appraisals Of Psychosismentioning
confidence: 98%